Evolution of aeronautical communications for personal and multimedia services. - Jahn, A. (IEEE Communications magazine)
The demand to make air travel more pleasant, secure, and productive for passengers is one of the winning factors for both airlines and the aircraft manufacturing industry for which aeronautical communications is one of the enablers. This article describes current trends in the area of aeronautical passenger communication toward personal and wireless in-cabin communications and multimedia data networks. Technological challenges are summarized as well as market potentials and regulatory issues.